Responsibilities of a Notary Public Violating the Code of Ethics Based on Decision Number 501/Pdt/2020/Pt.Dki And Decision Number 294 K/Tun/2021 - Carissa Dianputri; Rasji Rasji (Green Publisher Indonesia, 2024)
Notary is a public official who in its implementation makes an authentic deed where the authentic deed when made by a Notary is legally valid and can be used as a valid means of proof in the event of a dispute. Regulations related to Notaries have been regulated in Law Number 2 of 2014 Amendment to Law Number 30 of 2004 concerning Notary Offices. Notaries in carrying out their positions must also comply with the Notary Code of Ethics. As an example of a case taken in this author regarding a Tangerang city Notary named Muhammad Irsan was dishonorably dismissed because he signed outside his area of office and did not provide copies of the deed to the confronters. This type of research uses normative legal research with descriptive analysis. Secondary data used is through interviews, journals, books and laws and regulations. The results of the research are 1) The responsibility of the Notary in providing a copy of the deed to the visitors lies in Article 54 paragraph (1) of the Notary Position Law and 2) is a legal remedy that can be made by the visitors if the Notary violates his code of ethics, namely reporting or filing a lawsuit to the MPPN (Notary Central Supervisory Council). The confronters are entitled to their rights including the provision of copies of the deed from the Notary in accordance with Article 54 paragraph (1) of the UUJN.